Decreased Concentrations of Heparinoids Are Required to Inhibit Thrombin Generation in Plasma from Newborns and Children Compared to Plasma from Adults due to Reduced Thrombin Potential - Chan, Anthony K. C.; Berry, Leslie R.; Monagle, Paul T.; Andrew, Maureen (Thrombosis and Haemostasis, 2002)
Thrombin generation is decreased and delayed in plasma from newborns and children compared to adults. We hypothesized that lower doses of heparinoid anticoagulants are required to give similar thrombin generation in newborn (umbilical cord) and child plasmas compared to that of adults. Thrombin generation was performed in either the absence or presence of unfractionated heparin (UFH), low molecular weight heparin (LMWH) or a covalent antithrombin-heparin complex (ATH). After contact activation and recalcification of each plasma, thrombin activity was measured by periodic sub-sampling into chromogenic substrate. UFH inhibited thrombin generation to a greater extent compared to LMWH in all plasmas. Cord plasma was more sensitive to inhibition and displayed a greater difference in the effectiveness of UFH compared to LMWH than other plasmas. Lower concentrations of UFH and LMWH were required to inhibit thrombin generation in cord and child plasmas compared to adult plasma. In comparison, ATH strongly inhibited thrombin generation in all 3 plasmas. Similar peak thrombin concentrations were observed at lower ATH concentrations (0.1 U/mL) compared to either UFH (0.25 U/mL) or LMWH (0.25 U/mL). As with UFH and LMWH, cord plasma was more sensitive to inhibition by ATH than the other plasmas and lower ATH concentrations inhibited thrombin generation in cord and child plasmas compared to adult plasma. Decreased thrombin generation with heparinoids in cord and child plasmas compared to adult plasma coincided with decreased rates of prothrombin consumption and increased proportion of thrombin- α2-macroglobulin inhibitor complexes. In summary, lower doses of UFH, LMWH or ATH result in similar peak thrombin generation in newborn and child plasmas compared to adult plasma. Cord plasma was the most sensitive to inhibition, with ATH being more effective than UFH or LMWH.
Keywords: Heparin; thrombin; anticoagulant; newborn; plasma